Characteristics of Plasmodium vivax-infected erythrocyte rosettes. - Chotivanich, K; Pukrittayakamee, S; Simpson, J; White, N; Udomsangpetch, R (1998)
To investigate the rosette formation properties of Plasmodium vivax, blood was sampled from 26 adult Thai patients admitted with acute P. vivax malaria and a predominance of trophozoite and schizont stages in their peripheral blood smears. In each case, P. vivax-infected cells formed spontaneous rosettes with two or more uninfected red blood cells. Rosette formation of P. vivax was dependent on the divalent cations (Ca2+/Mg2+) and was highly sensitive to trypsin and heparin, but, unlike P. falciparum, rosettes of P. vivax did not reform after removal of heparin. Plasma taken from patients with either acute uncomplicated P. falciparum or P. vivax malaria reversed rosette formation of all P. vivax isolates whereas plasma from uninfected controls had no effect. There was a small but significant increase in rosette-reversing activity in plasma taken during the convalescent period (P < 0.001). The increment in reversal activity was significantly greater in plasma taken following recovery from P. vivax malaria compared with P. falciparum malaria. This suggests that P. vivax rosette reversal activity is antibody mediated and has both species-specific and cross-species components.